Analisis Penguasaan, Pemilikan, Penggunaan dan Pemanfaatan Tanah di Sempadan Pantai di Kelurahan Bintarore - Irsal Marsudi Sam; Setiowati Setiowati; Rakhmat Riyadi (Tunas Agraria, 2020)
Abstract: Most of the land beach border Village Bintarore has been controlled and owned by the community. The purpose of this research are (1) to know the kind of land tenure, land ownership, land use and land utilization; (2) Land Office Policy in Bulukumba Regency granting land rights; (3) the suitability of the land use and land utilization with RTRW. The research was conducted using qualitative methods for data analysis, survey and interview methods for data collection and the use of the census method. Based on the results of the study are known: (1) land on the beach border Village Bintarore is controlled by the Government, the public and legal entities. Types of landholdings consists of State land and land ownership rights. Type of land use consists of the use of the open land for housing, services, government agencies, religious services, rental services, workshop, warehousing, graves, sports field, industry, trade and services mix. Land utilization type consists of utilization as a place of residence, mix, economic, social, agricultural and not utilized; (2) Bulukumba District Land Office do policies to keep providing land rights in the area of the border of the Bintarore Village beach, (3) there are 87,19% mismatch between the use and utilization of land at Bintarore Village beach border with RTRW.Keywords: IP4T, RTRW, beach border. Intisari: Sebagian besar tanah sempadan pantai Kelurahan Bintarore telah dikuasai dan dimiliki oleh masyarakat. Tujuan penelitian untuk mengetahui (1) Jenis penguasaan, pemilikan, penggunaan dan pemanfaatan tanah; (2) Kebijakan Kantor Pertanahan Kabupaten Bulukumba dalam pemberian hak atas tanah; (3) Kesesuaian penggunaan dan pemanfaatan tanah dengan RTRW. Penelitian dilakukan menggunakan metode kualitatif, teknik pengumpulan data dilakukan melalui survei dan wawancara serta menggunakan metode sensus. Berdasarkan hasil penelitian diketahui: (1) Tanah di sempadan pantai Kelurahan Bintarore dikuasai oleh pemerintah, masyarakat dan badan hukum. Jenis pemilikan tanah terdiri dari tanah negara dan tanah hak milik. Jenis penggunaan tanah terdiri dari penggunaan untuk perumahan, tanah terbuka, jasa instansi pemerintah, jasa peribadatan, jasa sewa, perbengkelan, pergudangan, kuburan, lapangan olahraga, industri, jasa perdagangan dan kebun campuran. Jenis pemanfaatan tanah terdiri dari pemanfaatan sebagai tempat tinggal, campuran, ekonomi, sosial, pertanian dan tidak dimanfaatkan; (2) Kantor Pertanahan Kabupaten Bulukumba melakukan kebijakan untuk tetap memberikan hak atas tanah di kawasan sempadan pantai Kelurahan Bintarore (3) Terdapat 87,19% ketidaksesuaian antara penggunaan dan pemanfaatan tanah di sempadan pantai kelurahan Bintarore dengan RTRW.Kata Kunci: IP4T, RTRW, sempadan pantai.